Impact of sialyltransferase ST6GAL1 overexpression on different colon cancer cell types. (18th July 2019) - Venturi, Giulia; Gomes Ferreira, Inês; Pucci, Michela; Ferracin, Manuela; Malagolini, Nadia; Chiricolo, Mariella; Dall'Olio, Fabio
Abstract: Cancer-associated glycan structures can be both tumor markers and engines of disease progression. The structure Siaα2, 6Galβ1, 4GlcNAc (Sia6LacNAc), synthesized by sialyltransferase ST6GAL1, is a cancer-associated glycan. Although ST6GAL1 /Sia6LacNAc are often overexpressed in colorectal cancer (CRC), their biological and clinical significance remains unclear. To get insights into the clinical relevance of ST6GAL1 expression in CRC, we interrogated The Cancer Genome Atlas with mRNA expression data of hundreds of clinically characterized CRC and normal samples. We found an association of low ST6GAL1 expression with microsatellite instability (MSI), BRAF mutations and mucinous phenotype but not with stage, response to therapy and survival. To investigate the impact of ST6GAL1 expression in experimental systems, we analyzed the transcriptome and the phenotype of the CRC cell lines SW948 and SW48 after retroviral transduction with ST6GAL1 cDNA. The two cell lines display the two main pathways of CRC transformation: chromosomal instability and MSI, respectively. Constitutive ST6GAL1 expression induced much deeper transcriptomic changes in SW948 than in SW48 and affected different genes in the two cell lines. ST6GAL1 expression affected differentially the tyrosine phosphorylation induced by hepatocyte growth factor, the ability to grow in soft agar, to heal a scratch wound and to invade Matrigel in the two cell lines. These results indicate that the altered expression of a cancer-associated glycosyltransferase impacts the gene expression profile, as well as the phenotype, although in a cancer subtype-specific manner.